The donation: the mask - Vásquez, Carlos (Estudios de Filosofía, 1990)
The article consists in a proposal for reading Parmenides' Poem. In opposition to the exegesis made by traditional interpretations reducing it to immobilism, the author emphasizes an idea of speech that allows the acceptance of an irreductible difference between thing and word, the consequences of which are fundamental for thought: instead of the dialectic mode, the relation presence-absence is developed in a writing conceiving being as a donation (of meaning) and thought as a mask.